Comparison between Dexmedetomidine and Propofol for MRI Brain in Paediatric Patients- A Randomised Clinical Trial - Nazmeen Imranali Sayed; Naina Parag Dalvi; Urvi Hemant Desai; Bharati Tendolkar (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Dexmedetomidine is an α2 agonist that causes deep sedation after bolus, and can be given as infusion while performing Magnetic Resonance Imaging (MRI) brain in paediatric patients. There are reports of increased incidences of bradycardia and hypotension with prolonged recovery when it was used in high doses of 2-3 mcg/kg bolus. Lower dose of bolus may enhance the recovery profile and reduce the chances of bradycardia, while maintaining the efficacy of sedation. Aim: To compare the induction of sedation, haemodynamics stability, success rate of the scan, efficacy of the drug and recovery profile of low dose dexmedetomidine and propofol infusion for MRI brain in paediatric patients. Materials and Methods: This randomised clinical trial was conducted at Lokmanya Tilak Municipal General Hospital and Medical College, Sion Mumbai, Maharashtra, India, from November 2012 to April 2014. Total 70 American Society of Anaesthesiologist (ASA) grade I and II children aged 1-7 years posted for elective MRI brain were included in the study. Patients were divided into two groups i.e, dexmedetomidine group (n=35) and propofol group (n=35). Intranasal midazolam 0.2 mg/kg was given. Children in dexmedetomidine group were induced with 1 mcg/kg dexmedetomidine given over 10 minutes and maintained with dexmedetomidine at 1 mcg/kg/hr. Patients in propofol group received propofol bolus 2 mg/kg and infusion at 100 mcg/kg/min. Results: The MRI scan was completed in 34 (97.1%) and 35 (100%) of children in dexmedetomidine and propofol group, respectively. Time for complete recovery was 68.9±31.5 and 40.1±23 minutes in the dexmedetomidine and propofol group, respectively. Time for induction was 12.4±3.53 and 6.46±1.9 minutes in the dexmedetomidine and propofol group, respectively. Bradycardia was observed in 8 (22.9%) patients in dexmedetomidine group. Haemodynamic parameters were with 20% of baseline in both the groups. Conclusion: Propofol is a better anaesthetics in terms of recovery and induction time when used as an infussion for MRI brain in paediatric patients. Dexmedetomidine has a high incidence of bradycardia so requires a more vigilant monitoring.